Ecological predictors of academic satisfaction in senior secondary school students in Hong Kong: The mediating role of academic confidence - Dou, Diya; Shek, Daniel T. L.; Wong, Tingyin (Frontiers in Psychology, 2022)
Introduction Although the secondary school curriculum reform has taken place for more than 1 decade in Hong Kong, very few studies have examined senior secondary school students’ academic satisfaction and its predictors at the individual and school levels. The present study examined the influence of academic stress, school support, positive youth development (PYD) attributes on academic satisfaction via the mediation of academic confidence among senior secondary school students using three-wave longitudinal data. Methods This study was derived from a 6-year longitudinal project examining youth development among Hong Kong adolescents. Only three waves of data collected from 2,023 students, including 959 boys (47.4%) and 1,040 girls (51.4%), from grade 10 to 12 (i.e., Waves 4–6), were used in the present study focusing on senior high school years. Students responded to a questionnaire concerning different aspects of their development, including their perceptions of school support, PYD attributes, academic stress, academic confidence, and satisfaction with the NSS curriculum. We conducted structural equation modeling (SEM) to test the hypothesized model. Results Results showed that while Wave 4 academic stress negatively predicted academic satisfaction at Wave 6, Wave 4 positive youth development attributes and school support had positive associations with Wave 6 academic satisfaction; Wave 5 academic confidence also served as a mediator in these relationships, except for the relationship between school support and academic satisfaction. Discussion The theoretical, practical, and policy implications of the findings are discussed. The present study generally supports previous findings on the relationships between academic stress, school support, PYD attributes, academic confidence, and academic satisfaction. The findings emphasize the prominence of PYD attributes, school support, and confidence in enhancing students’ academic satisfaction.